MAPPING PATTERNS OF THE SPREAD OF COVID-19 IN MEDAN CITY IN EFFORTS TO IMPROVE HEALTH SERVICE ACTIONS TO COMMUNITIES EXPOSED TO THE COVID-19 VIRUS USING THE APRIORI ALGORITHM METHOD - wanra Tarigan; Thamrin Thamrin; Lismardiana Sembiring; Harlen Silalahi; Iswanto Sembiring (Jurnal Mantik, 2021)
Corona Virus Disease, also known as COVID-19, is an infectious disease caused by the recently discovered corona virus. Most people who contract COVID-19 will experience mild to moderate symptoms, and will recover without special treatment. The virus that causes COVID-19 is mainly transmitted through the droplets (saliva splashes) that are produced when an infected person coughs, sneezes, or exhales. These droplets are too heavy and cannot stay in the air, so they quickly fall and stick to the floor or other surface.It is easy to get infected so that many people are infected with COVID-19 so that there is an increase in service efforts in implementing the COVID-19 prokes in every sub-district in PemKO Medan. The Medan City Government seeks to cooperate with local health centers to tackle the spread of COVID-19 in Medan City by preparing COVID-19 alerts in every puskesmas in every sub-district.